Environmental Gaps in Commercial Advertising Policies in Sidoarjo Regency: Kesenjangan Lingkungan dalam Kebijakan Periklanan Komersial di Kabupaten Sidoarjo - Alif , Muhammad Wildan; Phahlevy, Rifqi Ridlo (Universitas Muhammadiyah Sidoarjo, 2024)
General background of this study examines the role of commercial advertising in marketing, particularly in Sidoarjo Regency. The specific background focuses on whether licensing policies for advertisements account for environmental sustainability. The knowledge gap is the lack of clear distinction between commercial and non-commercial advertisement regulations and their environmental impact. The aims are to analyze Sidoarjo’s advertising licensing procedures, including rules on placement and environmental considerations. The results indicate that while policies exist, unauthorized advertisements still cause environmental harm. The novelty is the focus on integrating environmental aspects into advertising policy. The implications suggest stricter enforcement to protect the environment. Highlights: Advertising licensing in Sidoarjo lacks clear distinction between commercial and non-commercial types. Unauthorized advertisements contribute to environmental degradation, especially in public spaces. Stronger enforcement and clearer guidelines can improve both regulatory compliance and environmental sustainability. Keywords: Advertising, Policy, Licensing, Environmental Sustainability